Individual differences in the effects of midazolam on anxiety-like behavior, learning, reward, and choice behavior in male mice - Jovita-Farias, Caio; Follett, Meagan E.; Dias-Junior, Behaim C.; Serra, Yasmim A.; Kisaki, Natali D.; Barros-Santos, Thaísa; de Jesus, Nailton M. S.; Rodrigues, Isa R. S.; Macedo, Larissa E. L.; Malpezzi-Marinho, Elena L. A.; Oliveira-Lima, Alexandre J.; Marinho, Eduardo Ary Villela; et al. (Frontiers in Psychiatry, 2023)
The aim of the present study was to investigate the behavioral effects of the benzodiazepine midazolam in male mice, in models of anxiolysis, learning, and abuse-related effects. In a first set of experiments, male Swiss mice were submitted to the training session of a discriminative avoidance (DA) task on the elevated plus maze to evaluate anxiety-like behavior and learning after vehicle or midazolam (1, 2 or 5 mg/kg, i.g.) administration. The same animals were submitted to a conditioned place preference (CPP) protocol with midazolam (1, 2 or 5 mg/kg, i.g.). In a second experiment, outbred (Swiss) and inbred (C57BL/6) male mice were submitted to a two-bottle choice (TBC) oral midazolam drinking procedure. Animals were exposed to one sucrose bottle and one midazolam (0.008, 0.016 or 0.032 mg/ml) plus sucrose bottle. Midazolam (1 and 2 mg/kg) induced anxiolytic-like effects, and all doses of midazolam prevented animals from learning to avoid the aversive closed arm during the DA training session. Assessment of midazolam reward via the CPP procedure and choice via the TBC procedure showed notable variability. A 2-step cluster analysis for the CPP data showed that midazolam data were well-fitted to 2 separate clusters (preference vs aversion), albeit with the majority of mice showing preference (75%). Correlational and regression analyses showed no relationship between midazolam reward and anxiolytic-like effects (time spent in the open arms in the DA test) or learning/memory. Two-step cluster analysis of the TBC data also demonstrated that, regardless of strain, mice overall fell into two clusters identified as midazolam-preferring or midazolam-avoiding groups. Both midazolam preference and avoidance were concentration-dependent in a subset of mice. Our findings show that midazolam preference is a multifactorial behavior, and is not dependent solely on the emergence of therapeutic (anxiolytic-like) effects, learning impairments, or on genetic factors (inbred vs outbred animals).